Flexural strength of autopolymerizing denture reline resins with microwave postpolymerization treatment - Vergani, Carlos Eduardo [UNESP]; Seo, R. S.; Pavarina, Ana Claudia [UNESP]; Reis, JMDN (Mosby, Inc, 2005)
Statement of problem. Microwave postpolymerization has been Suggested as a method to improve the mechanical strength of repaired denture base materials. However, the effect of microwave heating oil the flexural strength of the autopolymerizing denture reline resins has not been investigated.Purpose. This study analyzed the effect of microwave postpolymerization on the flexural strength of 4 autopolymerizing reline resins (Duraliner II, Kooliner, Ufi Gel Hard, and Tokuso Rebase Fast) and 1 heat-polymerized resin (Lucitone 550).Material and methods. For each material, 80 specimens (64 X 10 X 3.3 mm) were polymerized according to the manufacturer's instructions and divided into 10 groups (n = 8). Control group specimens remained as processed. Before testing, the specimens were Subjected to postpolymerization in a microwave oven using different power (500, 5,50, or 650 W) and time (3, 4, or 5 Minutes) settings. Load measurements (newtons) were made at a crosshead speed of 5 mm/min using a 3-point bending device with a span of 50 mill. The flexural strength values were calculated in MPa. Data analyses included 3-way and 2-way analysis of variance and the Tukey Honestly Significant Difference test (alpha=.05).Results. The flexural strengths of resins Duraliner 11 and Kooliner were significantly increased (P=.0015 and P=.0046, respectively) with the application of microwave irradiation using different time/power combinations. The materials Lucitone 550, Tokuso Rebase Fast, and Ufi Gel Hard demonstrated no significant strength improvement compared to the corresponding control. Only after microwave postpolymerization irradiation for 3 minutes at 550 W did Lucitione 550 show significantly higher flexural strength than Tokuso Rebase Fast and Ufi Gel Hard relining resins.Conclusion. Microwave postpolymerization irradiation can be an effective method for increasing the flexural strength of Duraliner II (at 650 W) and Kooliner (at 550 W and 650 W for 5 minutes).